Rice hull sodium ion battery carbon negative electrode material and preparation method thereof

By preparing agricultural waste rice husks into a carbon anode material for sodium ion battery with a porous structure, the problems of low capacity and poor circulation stability of existing sodium ion battery materials are solved, and efficient sodium ion storage and transfer are achieved, battery performance is improved and resource recycling is promoted.

CN119873821AInactive Publication Date: 2025-04-25FUJIAN SHIJI HUANA NEW ENERGY TECHNOLOGY GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510106044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing positive and negative electrode materials of sodium ion batteries have problems such as low capacity and poor cycle stability, which limits their wide application and development.

Method used

Using agricultural waste rice husks as raw materials, the carbon anode material of sodium husk ion battery with porous structure is prepared by mixing acid pretreatment, pre-carbonization, hydrothermal reaction of organic zinc acid and high-temperature carbonization. This method optimizes the pore structure by precisely controlling the carbonization temperature and heating rate, adjusts the pore structure, improves the specific surface area, and optimizes the pore structure through the synergistic action of hydrochloric acid and citric acid.

Benefits of technology

It significantly improves the capacity and first discharge efficiency of sodium ion batteries, improves the stability and charge transfer efficiency of materials, ensures the reliability of long-term use of materials, and realizes the resource recycling of waste rice husks, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255446330000081
    Figure BDA0005255446330000081
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery materials, in particular to a rice hull sodium-ion battery carbon negative electrode material and a preparation method thereof. The invention relates to a preparation method of a rice hull sodium ion battery carbon negative electrode material. The preparation method comprises the following steps: S1, mixed acid soaking and ultrasonic treatment; s2, pre-carbonization: carrying out pre-carbonization in an air atmosphere; s3, carrying out hydrothermal reaction on organic acid zinc; and S4, carbonization treatment is conducted, specifically, carbonization treatment is conducted under inert gas protection, the material can be prevented from being oxidized at the high temperature, and it is guaranteed that the carbonization process is conducted smoothly. And S5, carrying out acid pickling and vacuum drying to obtain the rice hull sodium-ion battery carbon negative electrode material. The preparation method provided by the invention not only improves the performance of the rice hull sodium ion battery carbon negative electrode material, but also realizes efficient utilization of resources, and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sodium ion battery materials, and in particular to a rice husk sodium ion battery carbon negative electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion battery is a secondary battery that mainly relies on the movement of sodium ions between the positive and negative electrodes to work. It is similar to the working principle of lithium-ion batteries and is one of the top ten emerging technologies in the field of chemistry in 2022. Sodium-ion batteries have attracted the attention of all parties and researchers due to their advantages such as abundant reserves and the same rocking chair storage mechanism. They are expected to become one of the candidates for large-scale energy storage devices in the future. Among the existing negative electrode materials for sodium-ion batteries, hard carbon negative electrode materials are more commonly used.

[0003] As the global energy crisis and environmental problems become increasingly serious, the development of clean and efficient new energy storage devices has become one of the research hotspots. Among them, sodium-ion batteries are considered to be one of the ideal choices to replace lithium-ion batteries due to their abundant raw materials and low cost. However, the positive and negative electrode materials of sodium-ion batteries currently on the market generally have problems such as low capacity and poor cycle stability, which limits their widespread application and development.

[0004] In order to improve the performance of sodium-ion batteries, researchers have proposed a variety of modification methods. For example, by doping foreign atoms to adjust the electronic structure of carbon materials, thereby improving their electrochemical properties; or using different precursor materials such as biomass, coal, petroleum coke, etc. to prepare carbon materials, in order to obtain better sodium storage capacity and cycle life. However, these methods either increase the cost of the materials, or the preparation process is complicated and difficult to large-scale industrial production. Although the above methods can improve the performance of sodium-ion batteries to a certain extent, due to the limitations of the materials themselves and the high requirements for preparation conditions, they lead to high costs and poor environmental performance, and cannot meet commercial needs. Summary of the invention

[0005] In order to realize the resource recycling of waste rice husks, the present application provides a rice husk sodium ion battery carbon negative electrode material and a preparation method thereof. First, agricultural waste rice husks are collected as raw materials, and after mixed acid pretreatment to remove impurities, the material is pre-carbonized and organic acid zinc is pore-formed through pyrolysis reaction, which is beneficial to increase the sodium storage space and capacity; and then by accurately controlling the carbonization temperature and heating rate of the waste rice husks, the pore structure of the rice husk sodium ion battery carbon negative electrode material is adjusted, which can significantly increase the specific surface area, and can effectively improve the capacity and first discharge efficiency of the sodium ion battery; finally, a mixed solution of hydrochloric acid and citric acid is used, and the synergistic effect of hydrochloric acid and citric acid is used to improve the pore structure of the rice husk sodium ion battery carbon negative electrode material, which can effectively improve the capacity and first discharge efficiency of the sodium ion battery. The preparation method of the present application is simple, suitable for large-scale production, and also realizes the resource recycling of waste rice husks, and improves the economic value of waste rice husks. In addition, based on the characteristics of rice husks rich in organic substances such as cellulose, hemicellulose and lignin, they are decomposed at high temperatures to generate carbon black-like substances. The material is then treated with an activator (zinc acid and a mixed solution of hydrochloric acid and citric acid) to expand the volume of micropores inside the material through chemical reactions, promote electrolyte penetration and enhance charge transfer efficiency. This porous structure not only facilitates the rapid diffusion of sodium ions into the material to achieve the embedding and de-embedding process, but also effectively alleviates the stress concentration caused by volume changes during charging and discharging, ensuring the reliability of the material for long-term use.

[0006] In a first aspect, the present application provides a method for preparing a carbon negative electrode material for a rice husk sodium ion battery, using the following technical solution: A method for preparing a carbon negative electrode material for a rice husk sodium ion battery comprises the following steps: S1. First, agricultural waste rice husks are collected as raw materials, the waste rice husks are added to a mixed acid solution and soaked for ultrasonic treatment for 4-8 hours, rinsed until the solution is neutral, and the treated waste rice husks are washed and dried to obtain a first precursor; S2, transferring the first precursor obtained in step S1 to a muffle furnace, and pre-carbonizing it under an air atmosphere to obtain a second precursor; S3, adding the second precursor obtained in step S2 and organic acid zinc into water in a mass ratio of 100:(1.0-3.0), stirring evenly, and performing hydrothermal reaction at 230° C. for 6-8 hours, filtering and drying, to obtain a third precursor; S4, subjecting the third precursor obtained in step S3 to carbonization treatment under an inert gas atmosphere, and obtaining a fourth precursor after natural cooling; S5. The fourth precursor is placed in an acid solution for pickling for 11-12 hours, and then vacuum dried at a temperature of 80-90° C. for 20-25 hours to obtain a rice husk sodium ion battery carbon negative electrode material.

[0007] By adopting the above technical scheme, S1: mixed acid soaking and ultrasonic treatment, impurities in rice husk, such as ash, residual pesticides, etc., can be effectively removed by soaking in mixed acid solution and ultrasonic treatment. Ultrasonic treatment helps the acid solution to penetrate more evenly into the rice husk and improve the treatment effect. The subsequent rinsing until the solution is neutral is to ensure that all acidic residues are completely removed to prevent unnecessary acidic effects from being introduced in subsequent steps. Drying is to remove excess water to facilitate the next step. This step lays a pure foundation for the entire preparation process and ensures the smooth progress of subsequent steps. S2: pre-carbonization, pre-carbonization in an air atmosphere can initially convert the organic matter in the rice husk into a carbon skeleton to form a preliminary pore structure. This step is crucial for the subsequent carbonization treatment because it can pre-adjust the porosity of the material to prepare for further carbonization. The pre-carbonization step and the subsequent carbonization step work together to finely control the pore structure of the final material, thereby optimizing its sodium storage performance. S3: hydrothermal reaction of organic acid zinc, in this step, the organic acid zinc is mixed with the second precursor and then hydrothermally reacted at a higher temperature. During the pyrolysis process, organic acid zinc decomposes and forms ZnO nanoparticles, which can serve as templates to promote pore formation inside the material, increase sodium storage space, and thus improve the capacity of the material. At the same time, the hydrothermal reaction also helps to form a more uniform carbon layer around the ZnO nanoparticles, further improving the conductivity and stability of the material. This step works synergistically with the pre-carbonization step. By controlling the reaction conditions (such as temperature and time), the pore structure and surface properties of the material can be precisely controlled, providing an ideal precursor for the subsequent carbonization treatment. S4: Carbonization treatment, which is carried out under the protection of inert gas, can prevent the material from being oxidized at high temperatures and ensure the smooth progress of the carbonization process. This step can further develop the carbon skeleton in the material to form a more stable porous structure. By controlling the carbonization temperature and heating rate, the pore size distribution and specific surface area of ​​the material can be adjusted to optimize its sodium storage performance. The carbonization step works together with the previous pre-carbonization and hydrothermal reaction steps to form a complete material modification process, ensuring that the final material has an ideal pore structure and high capacity characteristics. S5: Pickling and vacuum drying. The pickling step can further remove impurities in the material, especially incompletely reacted zinc salts and other metal oxides. Pickling can also adjust the pore structure of the material to make it more suitable for the embedding and deintercalation of sodium ions. Subsequent vacuum drying can ensure that the moisture in the material is completely removed to prevent performance degradation due to residual moisture. Pickling, combined with the previous carbonization step, can further optimize the pore structure and surface properties of the material, improve its sodium storage capacity and first discharge efficiency. At the same time, vacuum drying ensures the dryness of the material, providing a guarantee for the performance of the final product. In summary, the various steps cooperate with each other in the preparation process to form a complete process chain.By finely controlling the parameters of each step, rice husk sodium-ion battery carbon negative electrode materials with excellent sodium storage performance and high capacity characteristics can be prepared.

[0008] Preferably, in step S1, the mixed acid is prepared by mixing a hydrochloric acid solution and a hydrofluoric acid solution in a volume ratio of 2:1, the concentration of the hydrochloric acid solution is 1.4 mol / L, the concentration of the hydrofluoric acid solution is 0.8 mol / L, and the mass volume ratio of the waste rice husks to the mixed acid is 1 g:2-3 mL.

[0009] Preferably, in step S1, the drying process parameters are: drying temperature is 110-130°C, and drying time is 20-30h.

[0010] Preferably, in step S2, the process conditions for pre-carbonization are: when room temperature ≤ furnace temperature < 200°C, the temperature is increased at a rate of 6°C / min; when 200°C ≤ furnace temperature < 400°C, the temperature is increased at a rate of 2°C / min; when 400°C ≤ furnace temperature < 450°C, after carbonizing for 2-3 hours, it is naturally cooled to room temperature.

[0011] Preferably, in step S3, the organic acid zinc is at least one of zinc citrate, zinc oxalate and zinc malate.

[0012] Preferably, in step S4, the inert gas is one of nitrogen, argon and helium.

[0013] Preferably, in step S4, the process conditions of the carbonization treatment are: heating to 1250-1350°C at a heating rate of 3-5°C / min and keeping the temperature for 2-3h.

[0014] By adopting the above technical scheme, during the high-temperature carbonization process, organic matter in rice husks such as cellulose, hemicellulose and lignin will decompose into carbon black-like substances. At the same time, high temperature helps to remove residual volatile substances and impurities in the material to ensure the purity of the final product. The pore structure of rice husk carbon negative electrode materials can be adjusted by precisely controlling the carbonization temperature and heating rate. Higher carbonization temperatures (1250-1350°C) help to form stable micropores and mesoporous structures. These pores are not only conducive to the embedding and deintercalation of sodium ions, but also increase the specific surface area of ​​the material, thereby increasing the sodium storage capacity. The temperature and time of carbonization treatment have a significant effect on the electrochemical properties of the material. Appropriate high-temperature carbonization can significantly increase the specific surface area of ​​the material, which helps to improve the capacity and first discharge efficiency of sodium-ion batteries. In addition, by controlling the heating rate (3-5°C / min), internal stress concentration of the material caused by excessive heating can be avoided to ensure the structural integrity of the material. In summary, carbonization treatment plays a vital role in the preparation of rice husk sodium-ion battery carbon negative electrode materials. By precisely controlling the carbonization conditions, the electrochemical properties and sodium storage capacity of the materials can be significantly improved, while ensuring the structural stability and long-term reliability of the materials.

[0015] Preferably, in step S5, the mass volume ratio of the fourth precursor to the acid solution is 1 g:3-4 mL.

[0016] Preferably, in step S5, the acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2, the concentration of the hydrochloric acid solution is 1.8 mol / L, and the concentration of the citric acid solution is 0.6 mol / L.

[0017] By adopting the above technical scheme, the main function of the acid solution is to further optimize the pore structure of the carbon negative electrode material of the rice husk sodium ion battery through pickling, thereby improving its sodium storage capacity and first discharge efficiency. Specifically: the pickling process can remove impurities that may remain during the carbonization process, such as incompletely carbonized organic residues or other metal ions, to ensure the purity of the material. Through pickling, the pore structure of the material can be further adjusted and optimized to make it more suitable for the embedding and de-embedding of sodium ions, thereby increasing the specific surface area and pore volume of the material, and thus improving the sodium storage performance. Hydrochloric acid can effectively dissolve and remove impurities on the surface and in the pores of the material, especially metal ions. It can also moderately expand the pore size of the material and increase the pore connectivity through chemical corrosion. Citric acid is a weak acid with strong complexing ability. It can form stable complexes with certain metal ions in the material, making it easier to remove. In addition, citric acid can also prevent excessive corrosion to a certain extent and protect the microstructure of the material. When hydrochloric acid and citric acid are mixed in a certain proportion, they can produce a synergistic effect. The strong corrosiveness of hydrochloric acid combined with the complexing effect of citric acid can not only efficiently remove impurities, but also moderately regulate the optimization of pore structure. This synergistic effect allows the material to have high purity and stability while maintaining a good pore structure, thereby significantly improving the performance of sodium ion batteries. In summary, the role of the acid solution in step S5 and the synergistic effect between hydrochloric acid and citric acid are crucial for the preparation of high-performance rice husk sodium ion battery carbon negative electrode materials. Through this process, not only can the material be further purified, but its pore structure can also be optimized, thereby significantly improving the capacity and first discharge efficiency of the battery.

[0018] In the second aspect, the present application provides a rice husk sodium ion battery carbon negative electrode material, adopting the following technical scheme: As a general technical concept, the present application also provides the above-mentioned rice husk sodium ion battery carbon negative electrode material, which is prepared by the above-mentioned rice husk sodium ion battery carbon negative electrode material preparation method.

[0019] In summary, the beneficial technical effects of this application are: 1. Improve battery capacity: Impurities in rice husks are removed through mixed acid pretreatment, and the subsequent pre-carbonization and pyrolysis reaction of organic acid zinc can effectively form pores and increase sodium storage space, thereby significantly improving the capacity of sodium-ion batteries.

[0020] 2. Improve the first discharge efficiency: By precisely controlling the carbonization temperature and heating rate and adjusting the pore structure, the specific surface area can be significantly increased, which helps to improve the first discharge efficiency of sodium-ion batteries.

[0021] 3. Promote resource recycling: This method uses agricultural waste rice husks as raw materials, realizes the resource reuse of waste, enhances its economic value, and conforms to the concept of green production and sustainable development.

[0022] 4. Optimize pore structure: Use a mixed solution of hydrochloric acid and citric acid for pickling, and use the synergistic effect of the two to further improve the pore structure, which not only improves the capacity and first discharge efficiency, but also enhances the stability of the material.

[0023] 5. Enhance the charge transfer efficiency: Through the treatment of activator (organic acid zinc and mixed solution of hydrochloric acid and citric acid), the internal micropore volume of the material is expanded, the electrolyte penetration is promoted, the charge transfer efficiency is enhanced, and it is ensured that sodium ions can quickly diffuse into the interior of the material to achieve efficient embedding and de-embedding process.

[0024] 6. Improve material reliability: The design of the porous structure is not only conducive to the rapid diffusion of sodium ions, but also can effectively alleviate the stress concentration phenomenon caused by volume changes during charging and discharging, ensuring the reliability of the material in long-term use.

[0025] 7. Simplified production process: The entire preparation method is simple, suitable for large-scale production, reduces production costs and improves production efficiency. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] Example 1 A method for preparing a carbon negative electrode material for a rice husk sodium ion battery comprises the following steps: S1. First, agricultural waste rice husks are collected as raw materials, 10 kg of waste rice husks are added to 20 L of mixed acid solution and soaked in ultrasonic treatment for 4 hours, rinsed until the solution is neutral, and the treated waste rice husks are washed and dried at a drying temperature of 110° C. for 30 hours to obtain a first precursor; the mixed acid is prepared by mixing a hydrochloric acid solution and a hydrofluoric acid solution in a volume ratio of 2:1, the concentration of the hydrochloric acid solution is 1.4 mol / L, and the concentration of the hydrofluoric acid solution is 0.8 mol / L; S2, transferring the first precursor obtained in step S1 to a muffle furnace, and pre-carbonizing it in an air atmosphere to obtain a second precursor; the process conditions of the pre-carbonization are: when the room temperature is ≤ the furnace temperature < 200°C, the temperature is increased at a rate of 6°C / min; when 200°C is ≤ the furnace temperature < 400°C, the temperature is increased at a rate of 2°C / min; when the furnace temperature is 400°C, after carbonizing for 3 hours, it is naturally cooled to room temperature; S3, adding the second precursor obtained in step S2 and zinc citrate in a mass ratio of 100:1 into deionized water 3 times the mass of the second precursor, stirring evenly, and performing hydrothermal reaction at 230° C. for 6 h, followed by filtering and drying to obtain a third precursor; S4, heating the third precursor obtained in step S3 to 1250° C. at a heating rate of 3° C. / min under a helium atmosphere and keeping the temperature for 3 h, and then cooling naturally to obtain a fourth precursor; S5. Put 10 kg of the fourth precursor into 30 L of acid solution for pickling for 11 hours, and then vacuum dry it at a temperature of 80° C. for 20 hours to obtain a rice husk sodium ion battery carbon negative electrode material. The acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2. The concentration of the hydrochloric acid solution is 1.8 mol / L, and the concentration of the citric acid solution is 0.6 mol / L.

[0028] Example 2 A method for preparing a carbon negative electrode material for a rice husk sodium ion battery comprises the following steps: S1. First, agricultural waste rice husks are collected as raw materials, 10 kg of waste rice husks are added to 30 L of mixed acid solution and soaked in ultrasonic treatment for 8 hours, rinsed until the solution is neutral, and the treated waste rice husks are washed and dried at a drying temperature of 130° C. for 20 hours to obtain a first precursor; the mixed acid is prepared by mixing a hydrochloric acid solution and a hydrofluoric acid solution in a volume ratio of 2:1, the concentration of the hydrochloric acid solution is 1.4 mol / L, and the concentration of the hydrofluoric acid solution is 0.8 mol / L; S2, transferring the first precursor obtained in step S1 to a muffle furnace, and pre-carbonizing it in an air atmosphere to obtain a second precursor; the process conditions of the pre-carbonization are: when the room temperature is ≤ the furnace temperature < 200°C, the temperature is increased at a rate of 6°C / min; when 200°C is ≤ the furnace temperature < 400°C, the temperature is increased at a rate of 2°C / min; when the furnace temperature is 448°C, the temperature is kept for carbonization for 2 hours, and then naturally cooled to room temperature; S3, adding the second precursor obtained in step S2 and zinc oxalate in a mass ratio of 100:3 into deionized water 3 times the mass of the second precursor, stirring evenly, and performing hydrothermal reaction at 230° C. for 8 h, followed by filtering and drying to obtain a third precursor; S4, heating the third precursor obtained in step S3 to 1350° C. at a heating rate of 5° C. / min under an argon atmosphere and keeping the temperature for 2 h, and then cooling naturally to obtain a fourth precursor; S5. Put 10 kg of the fourth precursor into 40 L of acid solution for pickling for 12 hours, and then vacuum dry it at a temperature of 90° C. for 20 hours to obtain a rice husk sodium ion battery carbon negative electrode material, wherein the acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2, the concentration of the hydrochloric acid solution is 1.8 mol / L, and the concentration of the citric acid solution is 0.6 mol / L.

[0029] Example 3 A method for preparing a carbon negative electrode material for a rice husk sodium ion battery comprises the following steps: S1. First, agricultural waste rice husks are collected as raw materials, 10 kg of waste rice husks are added to 25 L of mixed acid solution and soaked in ultrasonic treatment for 6 hours, rinsed until the solution is neutral, and the treated waste rice husks are washed and dried at a drying temperature of 120° C. for 25 hours to obtain a first precursor; the mixed acid is prepared by mixing a hydrochloric acid solution and a hydrofluoric acid solution in a volume ratio of 2:1, the concentration of the hydrochloric acid solution is 1.4 mol / L, and the concentration of the hydrofluoric acid solution is 0.8 mol / L; S2, transferring the first precursor obtained in step S1 to a muffle furnace, and pre-carbonizing it in an air atmosphere to obtain a second precursor; the process conditions of the pre-carbonization are: when the room temperature is ≤ the furnace temperature < 200°C, the temperature is increased at a rate of 6°C / min; when 200°C is ≤ the furnace temperature < 400°C, the temperature is increased at a rate of 2°C / min; when the furnace temperature is 430°C, the temperature is kept for carbonization for 2.5 hours, and then naturally cooled to room temperature; S3, adding the second precursor obtained in step S2 and zinc malate in a mass ratio of 100:2 into deionized water 3 times the mass of the second precursor, stirring evenly, and performing hydrothermal reaction at 230° C. for 7 h, followed by filtering and drying to obtain a third precursor; S4, heating the third precursor obtained in step S3 to 1310° C. at a heating rate of 4° C. / min under a nitrogen atmosphere and keeping the temperature for 2.5 h, and then cooling naturally to obtain a fourth precursor; S5. Put 10 kg of the fourth precursor into 35 L of acid solution for pickling for 12 hours, and then vacuum dry it at a temperature of 85° C. for 23 hours to obtain a rice husk sodium ion battery carbon negative electrode material, wherein the acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2, the concentration of the hydrochloric acid solution is 1.8 mol / L, and the concentration of the citric acid solution is 0.6 mol / L.

[0030] Comparative Example 1 The same as Example 3, except that: in step S5, the acid solution is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 1.8 mol / L.

[0031] Comparative Example 2 The same as Example 3, except that: in step S5, the acid solution is a citric acid solution, and the concentration of the succinic acid solution is 0.6 mol / L.

[0032] Comparative Example 3 The method is the same as Example 3, except that: there is no step S3, and the second precursor in step S2 is directly heated to 1310°C at a heating rate of 4°C / min under a nitrogen atmosphere and kept at that temperature for 2.5h, and then cooled naturally to obtain a fourth precursor.

[0033] Comparative Example 4 The same as Example 3, except that: in step S4, the temperature is increased to 1310°C at a heating rate of 1.5°C / min and kept at that temperature for 2.5h.

[0034] Comparative Example 5 The same as Example 3, except that: in step S4, the temperature is increased to 1310°C at a heating rate of 7°C / min and kept at this temperature for 2.5h.

[0035] Performance Testing 1. The rice husk sodium ion battery carbon negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were respectively made into the following sodium ion batteries and tested. The test results are shown in Table 1.

[0036] Rice husk sodium ion battery carbon negative electrode material, conductive agent Super P and carboxymethyl cellulose were mixed with water in a ratio of 8:1:1 to form a slurry, stirred for 24 hours, coated on carbon-coated aluminum foil, and dried in an oven at 80°C for 24 hours. The dried electrode was cut into 12mm discs with a loading of 1-1.4mg / cm 2 , using sodium foil as the counter electrode, pressed into a sodium ion battery. Charge and discharge test conditions: constant current charge and discharge, current density 30mA / g, voltage range 0.01V to 2.00V.

[0037] The test method of capacity retention rate is as follows: 500 cycles at room temperature 0.2C (1C = 260 mAh / g).

[0038] 2. Use the Best Instruments fully automatic nitrogen adsorption BET specific surface area tester BSD-BET400 to measure the specific surface area of ​​the carbon negative electrode material of rice husk sodium ion battery.

[0039] Table 1 Electrochemical performance test results Analyzing the data in Table 1, we can see that: 1) The carbon negative electrode material of rice husk sodium ion battery prepared in Example 1-Example 3 is made into a sodium ion battery, and its first discharge capacity, first discharge efficiency, capacity retention rate and specific surface area are all high. It shows that the present application first collects agricultural waste rice husk as raw material, removes impurities through mixed acid pretreatment, and then forms pores inside the material through pre-carbonization and organic acid zinc pyrolysis reaction, which is beneficial to increase the sodium storage space and capacity; and then by accurately controlling the carbonization temperature and heating rate of the waste rice husk, adjusting the pore structure of the carbon negative electrode material of the rice husk sodium ion battery, the specific surface area can be significantly increased, and the pore volume can be reduced, which can effectively improve the capacity and first discharge efficiency of the sodium ion battery; finally, a mixed solution of hydrochloric acid and citric acid is used, and the synergistic effect of hydrochloric acid and citric acid can be used to improve the pore structure of the carbon negative electrode material of the rice husk sodium ion battery, which can effectively improve the capacity, first discharge efficiency and capacity retention rate of the sodium ion battery.

[0040] 2) The performance comparison analysis of the rice husk sodium ion battery carbon negative electrode material prepared by Example 3 and Comparative Examples 1-2 shows that the acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2, and the pore structure of the rice husk sodium ion battery carbon negative electrode material is further optimized by pickling, thereby improving its sodium storage capacity, first discharge efficiency and capacity retention rate. When hydrochloric acid and citric acid are mixed in a certain proportion, a synergistic effect can be produced between them. The strong corrosiveness of hydrochloric acid combined with the complexing effect of citric acid can not only efficiently remove impurities, but also moderately regulate the optimization of the pore structure. This synergistic effect enables the material to have a high purity and stability while maintaining a good pore structure, thereby significantly improving the overall performance of the sodium ion battery.

[0041] 3) The performance comparison analysis of the rice husk sodium ion battery carbon negative electrode material obtained in Example 3 and Comparative Example 3 shows that in step S3, after the organic acid zinc is mixed with the second precursor, a hydrothermal reaction is carried out at a higher temperature. The organic acid zinc will decompose and form ZnO nanoparticles during the pyrolysis process. These nanoparticles can be used as templates to promote pore formation inside the material, increase sodium storage space, and thus increase the capacity of the material. At the same time, the hydrothermal reaction also helps to form a more uniform carbon layer coated around the ZnO nanoparticles, further improving the conductivity and stability of the material, and ultimately helping to improve the capacity, first discharge efficiency and capacity retention rate of the sodium ion battery.

[0042] 4) The comparative analysis of the performance of the rice husk sodium ion battery carbon negative electrode material obtained in Example 3 and Comparative Examples 4-5 shows that by controlling the heating rate, the internal stress concentration of the material caused by excessive heating can be avoided, the structural integrity of the material can be ensured, and the electrochemical properties and sodium storage capacity of the material can be improved, while ensuring the structural stability and comprehensive performance of the material.

[0043] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a carbon negative electrode material for a rice husk sodium ion battery, characterized in that: The following steps are involved: S1. First, agricultural waste rice husks are collected as raw materials, the waste rice husks are added to a mixed acid solution and soaked for ultrasonic treatment for 4-8 hours, rinsed until the solution is neutral, and the treated waste rice husks are washed and dried to obtain a first precursor; S2, transferring the first precursor obtained in step S1 to a muffle furnace, and pre-carbonizing it under an air atmosphere to obtain a second precursor; S3, adding the second precursor obtained in step S2 and organic acid zinc into water in a mass ratio of 100:(1.0-3.0), stirring evenly, and performing hydrothermal reaction at 230° C. for 6-8 hours, filtering and drying, to obtain a third precursor; S4, subjecting the third precursor obtained in step S3 to carbonization treatment under an inert gas atmosphere, and obtaining a fourth precursor after natural cooling; S5. The fourth precursor is placed in an acid solution for pickling for 11-12 hours, and then vacuum dried at a temperature of 80-90° C. for 20-25 hours to obtain a rice husk sodium ion battery carbon negative electrode material.

2. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S1, the mixed acid is prepared by mixing a hydrochloric acid solution and a hydrofluoric acid solution in a volume ratio of 2:1, the concentration of the hydrochloric acid solution is 1.4 mol / L, the concentration of the hydrofluoric acid solution is 0.8 mol / L, and the mass volume ratio of the waste rice husk and the mixed acid is 1 g:2-3 mL.

3. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S1, the drying process parameters are: drying temperature is 110-130°C, and drying time is 20-30h.

4. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S2, the pre-carbonization process conditions are: when room temperature ≤ furnace temperature < 200°C, heat at a rate of 6°C / min; when 200°C ≤ furnace temperature < 400°C, heat at a rate of 2°C / min; when 400°C ≤ furnace temperature < 450°C, carbonize for 2-3 hours and then cool naturally to room temperature.

5. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S3, the organic acid zinc is at least one of zinc citrate, zinc oxalate and zinc malate.

6. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S4, the inert gas is one of nitrogen, argon and helium.

7. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S4, the process conditions of the carbonization treatment are: heating to 1250-1350°C at a heating rate of 3-5°C / min and keeping the temperature for 2-3h.

8. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S5, the mass volume ratio of the fourth precursor and the acid solution is 1 g:3-4 mL.

9. The method for preparing a carbon negative electrode material for a rice husk sodium ion battery according to claim 1, characterized in that: In step S5, the acid solution is prepared by mixing a hydrochloric acid solution and a citric acid solution in a volume ratio of 3:2, the concentration of the hydrochloric acid solution is 1.8 mol / L, and the concentration of the citric acid solution is 0.6 mol / L.

10. A rice husk sodium ion battery carbon negative electrode material, characterized in that: The rice husk sodium ion battery carbon negative electrode material is prepared by the method for preparing the rice husk sodium ion battery carbon negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of rice hull derivative hard carbon, material produced thereform, and application thereof

    CN107500263A

  • Hard carbon negative electrode material of sodium-ion battery based on shell biomass and preparation method of hard carbon negative electrode material

    CN113666356A

  • Preparation method of hard carbon negative electrode material for sodium ion battery

    CN117602609A

  • Positive electrode material, biomass synthesis method thereof and lithium ion battery

    CN118145708A

  • Dragon fruit branch derived hard carbon material, preparation method thereof and sodium ion battery

    CN118439590A